(untitled) (Actualizaciones en Sida e Infectología, 2025)
St.pneumoniae is a common agent causing both upper and lower respiratory diseases. Its role in abdominal infection is rare, even more bile duct infection.We report a case of cholangitis due to St.pneumoniae in a patient with esophageal cancer and bile duct instrumentation.